The Image of Modernism in the History of Islamic Intellectualism in Indonesia - Amin, Faizal; Masuwd, Mowafg; Fauzan, Fauzan (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2024)
The classification of modernist versus traditionalist, is no longer appropriate to describe the spectrum of contemporary Islamic intellectualism. This article analyzes how the concept of modernism is defined and elaborated by Indonesian Islamic scholars. It also , in particular, examines the dynamics of Islamic modernism growth that have shaped the distinctive characteristics of Indonesian Islam compared to those in other Southeast Asian countries. This article come from library research using a qualitative approach for data collection and analysis. By an emphasis on document and text analysis, in particular, this article shows that modernism in the history of Islamic intellectualism in Indonesia could be imaged as axis of dialectical discourse in the formation of Indonesian Islamic characteristics; moderate and flowering Islam. This article, in particular, argues that the emergence of modernism in Islam plays a role in confirming the existence of Indonesian Islam as an integral, not peripheral, part of the Islamic world civilization.